1975
DOI: 10.1002/pol.1975.170130607
|View full text |Cite
|
Sign up to set email alerts
|

Formation of free radicals in photoirradiated cellulose. I. Effect of wavelength

Abstract: Formation of free radicals in photoirradiated cellulose has been studied by means of ESR spectroscopy at 77°K. Three kinds of light sources with different wavelengths between 2500 and 4000 ÅR were employed. No radicals detectable by ESR were recorded when cellulose was irradiated with light of wavelength longer than 3300–3400 ÅR. Hydrogen atoms that generated a doublet spectrum (ΔH = 508 G) were observed when cellulose was irradiated with light longer than 2800 ÅR. Hydrogen atoms and formly radicals that gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1975
1975
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Hon 964) investigated in detail the effect of wavelength for the formation of free radicals in photo-irradiated cellulose. No radicals were detected by ESR recordings when cellulose was irradiated with light of wavelength longer than 3300-3400 A.…”
Section: Esr Study Of Degradation Processes In Polymersmentioning
confidence: 99%
“…Hon 964) investigated in detail the effect of wavelength for the formation of free radicals in photo-irradiated cellulose. No radicals were detected by ESR recordings when cellulose was irradiated with light of wavelength longer than 3300-3400 A.…”
Section: Esr Study Of Degradation Processes In Polymersmentioning
confidence: 99%
“…Ref. 24). A comparison with previous investigations 25 indicated only some obvious differences in experimental spectra recorded at 77 K (Fig.…”
Section: Cellulosementioning
confidence: 77%
“…In addition, other cellulose degradation studies have observed an absorbance peak at 260 nm as a result of ultraviolet photolytic degradation (Yatagai and Zeronian 1994), enzymatic hydrolysis (Patel et al 1993), and acid hydrolysis (Kalinina et al 2001). This peak was assigned to a weak chromophore associated with acetal groups, which form the linkages between glucose residues in cellulose (Hon 1975). We determined that mechanical disruption of bacterial cellulose released small soluble cellulose fragments which absorb at 260 nm.…”
Section: Characterization Of Oxidized Compositementioning
confidence: 93%